Tennis serve analysis using on-the-field markerless motion capture - Corazza, S.; Sheets, A.; Abrams, G.; Safran, M.; Andriacchi, T. P. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Recent tennis studies (Elliot et al. 2003) have demonstrated how injuries are often related to the serve, in particular for the shoulder joint. Different types of serves, e.g. the flat and the kick types, may involve different kinematics and different musculoskeletal demands at the joints, that play an important role in the development of long term injuries (Reid et al. 2007). It has been difficult to study this problem because a rigorous analysis of the mechanics of the tennis serve has been encumbered by the need for placing markers or fixtures on the body to accurately capture the movement. This study examines the application of a newly developed Markerless Motion Capture (MMC) (Corazza, 2006, Mundermann, 2006) method for performing a full-body 3D kinematic analysis on the tennis court. Differences between the flat and the kick serve are analyzed by comparing joint kinematics, and velocities of joint centers (JC) and the racket.